A new marker antibody (the MM antibody) for primary biliary cirrhosis-chronic active hepatitis overlap patient - Hiwatashi, Tsunenori; Miki, Makoto; Takano, Saeko; Karasawa, Eii; Miyachi, Kiyomitsu; Matsushima, Hiroshi (Japanese Journal of Clinical Immunology, 1988)
An uncharacterized antibody was found in a patient afflicted with primary biliary cirrhosis or chronic active hepatitis. This antibody (which we tentatively called the MM antibody) could be detected by means of double immunodiffusion using the microsomal fraction of rat liver as the antigen. However, cytoplasmic staining in both rat liver and kidney could not be obtained when viewed by indirect immunofluorescent microscopy. The MM antibody did not react with mitochondrial fraction of rat liver. The antibody showed nonidentity with anti-liver kidney microsome antibodies when tested by means of double immunodiffusion. It was found in 5 of 5 PBC-CAH overlap patients who were diagnosed histopathologically, 3 of 19 PBC patient sera and in 2 of 14 CAH patient sera. However, it was not found in non-autoimmune hepatitis patients, nor in the healthy subjects. In conclusion, the detection of MM antibody might be useful for the diagnosis of autoimmune liver diseases particularly, PBC-CAH overlap patient.